PENISILIN G ASILASE DARI SEL TRANSFORMAN HASIL TRANSFER DNA ESCHERICHIA COLI B130 KE DALAM SEL E. COLI HB101 - Bartholomeus, Heru
The production of penicillin G acylase enzyme could be increased by 25 times, by cloning multiple-recombined chromosomal DNAs of E. coli B130 with pBR322 plasmids, into E. cols HB101 as host cell. Consequently, the treatment also affected the optimum catalytic temperature and biosynthetic properties of the enzyme. The optimum catalytical temperature of the enzyme produced by E. coli B130 was 37 Â°C, whereas it was 65 Â°C in that produced by engineered cells. Biosynthetic properties of the enzyme changed from inductive to partially-constitutive in E. coil B130 and E. coil SC165, respectively. The enzyme produced by E. coli SC165 cells could be purified as many as 5 times by an ammonium sulphate fractionation proceeded with dialysis. On the other hand, by using an anion exchanger column chromatography on DEAE-cellulose, it could be purified up to 11 times. The stability of the enzyme toward temperature and pH changes and storing periods could be increased by immobilizing it in a polyacrylamide, by which the catalytical power and kinetic properties of it would be influenced. The Km values of free and immobilized enzymes are 0, 807 mM and 9.663 mM, while Vmax values of them are 15.346 umol 6-APA/mg protein/25 minutes and 13.385 umol 6 APA/mg protein/60 minutes, respectively. Phenylacetic acid was found to be a competitive inhibitor for the enzymes both free and immobilized, with their inhibition constants (Ki) are 21.433 mM and 192.623 mM, respectively. Besides that, benzilpenicillin was also shown an inhibition effect with a constant of 279.897 mM to the free enzyme.